Discovery of Posture Secret in the Treatment of Persistent Genital Arousal Disorder/Genito-pelvic Dysesthesia: a Case Report and Literature Review - Yunxu ZHANG, Li SU, Yanyun Xing, Xiaolin LIU, Qiang WANG (Zhongguo quanke yixue, 2022)
Persistent genital arousal disorder (PGAD) and genito-pelvic dysesthesia (GPD) jointly known as persistent genital arousal disorder/genito-pelvic dysesthesia syndrome (PGAD/GPD) , which was a unique disorder characterized by spontaneous or secondary genital arousal and dysesthesia in the genital and pelvic areas discovered abroad in recent years. In addition, no relevant reports on PGAD/GPD have been found in CNKI, WanFang Data, and VIP. Discovery of posture secret (DPS) is a manual therapy technique with the 4R principle as the core developed from the integration of various mainstream posture correction techniques in the world, which has unique curative effect on improving musculoskeletal pain and abnormal posture. This article reports a domestic case of complete remission of symptoms of PGAD/GPD treated with DPS, and reviews relevant foreign literature on PGAD/GPD, in order to raise the attention of domestic peers.